The genus Hecabolus Curtis 1834 (Braconidae: Doryctinae) in South America, with description of six new species - de Castro, Clóvis Sormus; Zaldívar-Riverón, Alejandro; Briceño-G., Rosa; Penteado-Dias, Angélica Maria (Zootaxa, 2013)
Six new species of the doryctinae wasp genus Hecabolus Curtis 1834 (Braconidae) are described from Brazil and Vene-zuela: H. assis sp. nov., H. julianoi sp. nov., H. robustus sp. nov., H. semiaridus sp. nov., H. shimborii sp. nov., and H. sulmatogrossensis sp. nov. A key to the nine described species of Hecabolus is provided.